Analysis of economic growth in tourism under the impact of terrorism and of the waves of refugees - Gina Ionela Butnaru; Marilena Mironiuc; Carmen Huian; Alina Petronela Haller (Amfiteatru Economic Journal, 2018)
Tourism is an extremely complex phenomenon marked by major factors like the terrorist attacks and the refugees' invasion (the recent waves of migrants). This paper tests by empirical analyses if in the European Union countries, the gross domestic product in tourism reacts to the situations of crisis caused by the terrorist attacks and by the waves of refugees. The techniques used are σ and β convergence tests, combined with the deterministic sensitivity analysis. The sample consists of 26 European Union countries studied between 2000-2015 and 2000-2016, according to the available data. The results prove the prevalence of divergence, explicable by the existence of some countries, in the structure of the groups analysed, which have different contributions of gross domestic product in tourism to their overall economic growth. At the same time, a higher reaction of gross domestic product in tourism per capita is identified under the influence of the number of terrorism victims, compared to the incidence of the variation of the number of refugees. However, it cannot be stated that the two phenomena lead to the general tendency of decrease of the gross domestic product in tourism per capita. On the contrary, there are occasional regressions of this indicator, which can be correlated only subsidiary with the crisis situations caused by terrorism and the waves of refugees.
Keywords: Z39; O11; O47; N94; E13; 330; tourism; convergence; sensitivity analysis; terrorist attacks; refugees' invasion